(Un-)becoming Chinese creatives: transnational mobility of creative labour in a 'global' Beijing. Issue 4 (4th July 2019) - Lin, Jian
ABSTRACT: Drawing on qualitative research conducted on transnational creative workers in Beijing, this article shows how the vibrant interaction between global cultural industries and the local Chinese economy propels transnational labour mobility and affects the subjectification of transnational creative workers. Having come to China to enhance their careers, these professionals have been incorporated into the Chinese creative workforce, contributing to the Party State's aspiration to use creativity as a growth engine for the economy and as a form of soft power. In terms of these workers' everyday experience, however, China's aspiration to 'foreign creativity' does not necessarily guarantee a privileged life. The State's restrictions on migration and the insecure working circumstances within the Chinese creative workplace discourage these transnationals from fully integrating in Chinese society and the Chinese labour market. At the same time, this research shows that the precarious lives led by transnational creative workers in Beijing are also productive and generate the conditions for a situated cosmopolitan subjectivity. Such a cosmopolitan subjectivity fosters respect for cultural difference and relations of mutual understanding and care among both international and local subjects.